Possible Antinociceptive Mechanism and Site of Activity of Haruan (Channa Striatus) Crude Aqueous Extract in Mice - Zakaria, Zainul Amiruddin (2005)
The present study was carried out to determine the possible mechanism of antinociception and site of activity of the crude aqueous extract of Haruan (Channa striatus) (ASH) in mice using the abdominal constriction test. The ASH, obtained after chloroform:methanol (CM) (2:l; vlv) extraction (24 hrs) of the fresh Haruan fillet, was evaporated to remove the methanol residue and used throughout the study. The first study was carried out to ascertain the dry weight and antinociceptive profile of ASH. The second study was carried out to determine the amino acids and fatty acids compositions, as well as the polypeptide profile of ASH. The third study was carried out to determine the actual onset and offset of ASH activity after its subcutaneous (SC) or intraperitoneal (IP) administration at four different sets of time (0, 5, 30 and 60 min). The fourth and fifth studies were carried out to determine the involvement of opioid and non-opioid receptors, respectively, in the ASH antinociceptive activity. All of the antagonists of opioidergic, muscarinic, nicotinic, a- and P-adrenergic, dopaminergic, serotonergic and y-aminobutyric acid (GABA) receptors were administered (SC) 10 min prior to ASH (SC) administration. The sixth study was carried out to determine the role of L argininelnitric oxide/cyclic 3'5'-guanosine monophosphate (L-arginine/NO/cGMP) pathway in the ASH antinociceptive activity. The precursor (L-arginine) and inhibitor @IG-nitro-L-arginine methyl esters (L-NAME)) for NO, as well as the inhibitor for cGMP (methylene blue (MB), were administered (SC) 5 min before ASH administration (SC). In all of the above-mentioned studies that involved the use of antinociceptive test, the 0.6% acetic acid-induced abdominal constriction test in mice was used as an assay to evaluate the ASH antinociceptive activity. All data obtained were analysed using the One-way Analysis of Variance (ANOVA) followed by the Tukey test with P<0.05 as the limit of significance. From the data obtained, the ASH, which exhibited significant (P<0.05) and concentration/dosage-dependent antinociceptive activity, yielded 1.89g/10.0ml of white coloured powder after subjection to the freeze-drying process. The ASH was also found to contain all the important amino acids with major amino acids found are glycine (35.77% -+ 0.58), alanine (10.19% + 1.27), lysine (9.44 + 0.56), aspartic acid (8.53 -+ 1.15) and proline (6.86% -+ 0.78). Furthermore, the ASH was also found to contain high composition of palmitic acid (C16:O) (35.93% * 0.63), oleic acid (C18: 1) (22.96% A 0.40), stearic acid (C18:O) (15.31% * 0.33), linoleic acid (C18:2) (1 1.45% * 0.3 1) and arachidonic acid (C20:4) (7.44% rt 0.83). The ASH was also found to produce at least four major fractions (at the retention times of 8.919, 9.841, 10.263 and 10.744), when subjected to the high performance liquid chromatography (HPLC) process, that are believed to be polypeptides. The onset time and the offset time of the ASH antinociceptive activity, which are concentration-dependent and concentration independent, occurred between 0 to 5 min, and 60 min after its SC administration. Interestingly, changing the route of administration from SC to IP caused significant (Pc0.05) increase in the ASH antinociceptive activity with the concentration-independent onset time of activity observed immediately after the ASH administration with no apparent offset time. The activity was found to reach the maximum effect 30 min after the ASH administration regardless of the route of administration used. Pretreatment with naloxone at all dosages did not cause any significant changes in the ASH antinociceptive activity indicating that the activity did not involve an opioid receptor mechanism, and thus confirmed the report made by Dambisya et al. (1999). Re-treatment with various types of non-opioid receptor antagonists demonstrated the involvement of at least four =of receptors (muscarinic, GABA*, a-adrenergie d s e r o t o ~ g k ) in the mechanism of ASH antinociceptive activity. Pre-treatment with atropine and bicuculine almost completely blocked (P<0.05), while pre-treatment with phenoxybenzamine and methysergide significantly (Pc0.05) reduced half of the ASH activity. The role of Larginine/ NO/cGMP pathway in ASH antinociceptive activity was also observed after pretreatment of the ASH with L-arginine, L-NAME or MB, but not with D-arginine. Pretreatment with L-arginine was found to significantly (PC0.05) reduce the ASH antinociceptive activity, whereas pretreatment with L-NAME or MB were found to enhance (Pc0.05) the activity. Based on the finding, low concentration of NO, limited by the presence of higher concentration of ASH, and inhibition of cGMP system play important role in ASH antinociceptive activity. However, the actual mechanism underlying this phenomenon is yet to be fully understood.As a conclusion, we suggest that the ASH-produced antinociceptive activity could be due to the presence of various types of amino acids and fatty acids, as well as four major fractions, and involved activation of at least four types of the non-opioid receptors (namely the muscarinic, GABA*, a-adrenergic and serotonergic) and the Larginine/ NO/cGMP pathway.